Case report: Clinical and genetic features of pediatric choroidal melanoma - Valente, Paola; Galardi, Angela; Di Giannatale, Angela; Romanzo, Antonino; Novelli, Antonio; Orlando, Valeria; Colletti, Marta; Russo, Ida; De Vito, Rita; Iarossi, Giancarlo; Petroni, Sergio; Sinibaldi, Lorenzo; et al. (Frontiers in Medicine, 2025)
Uveal melanoma (UM) is the second most common type of primary melanoma in adults, but it is extremely rare in children. We report a 12-year-old boy with a rare juvenile case of UM characterized by specific clinical and genetic features, including eye imaging and cytogenetic analysis. The tumor was analyzed using immunohistochemistry in order to confirm the clinical diagnosis and using next-generation sequencing (NGS) in order to investigate the correlation between pathological features and prognosis. The NGS revealed a somatic mutation in the GNAQ gene. Furthermore, we established a primary cell line (Opbg-UM1) to better understand the biology of this tumor in the pediatric setting. However, our case identified several factors predictive of poor prognosis, such as tumor proximity to the fovea and optic disc, large size, lack of pigmentation with mushroom configuration in category T2, and a complex karyotype showing numerical abnormalities on chromosome 6 and a mosaic loss of the Y chromosome in blood and in the primary cell line. This mutation may represent a poor prognostic factor in older children with UM.